The impact of Non-Tariff Measure on trade in the case of 12 Arab countries - Narmen M. Ghafor; Masoud Ali Khalid (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Non-tariff measures such as food safety and technical standards can be used to obtain the non-trade goal of protecting the safety and health of consumers. On the other hand, they can also be used as a trade-safe tool to drive a price gap between domestic and foreign producers. This study investigates the impacts of NTMs on trade for 12 Arabic countries over the period of 1999-2014 with a specific focus on animals, vegetable, vehicle, Plastic, Population, distance and Language. We employ theoretical framework of gravity model by applying panel data estimation. Our results indicate that animal, vehicle and population variables are positive and statistically significant. Meaning that our three variables have a positive impact on GDP, in other words, three variables are supportive tools to GDP and economic growth in the Arabian countries.